2018
DOI: 10.1292/jvms.18-0119
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of pharmacological responses to anti-diabetic drugs in female Spontaneously Diabetic Torii (SDT) fatty rats, a new nonalcoholic steatohepatitis (NASH) model

Abstract: Nonalcoholic steatohepatitis (NASH) is a progressive liver disease, and some patients develop hepatic cirrhosis/carcinoma. Animal models play key roles in the development of new therapies for NASH. In this study, the pharmacological effects of metformin and pioglitazone were investigated in female Spontaneously Diabetic Torii (SDT) fatty rats to verify the utility of this model. The anti-diabetic drugs were administered to SDT fatty rats fed a cholesterol-enriched diet from 4 to 25 weeks, and changes in food i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Spontaneously Diabetic Torii Lepr fa (SDT fatty) rats were established by transferring the fa allele of the Zucker fatty rat into the genome of the nonobese SDT rat. The SDT fatty rat shows hyperphagia, obesity, hyperglycaemia, and dyslipidaemia, so it can be considered a new model for obese type 2 diabetes . However, the details of the haemodynamics in SDT fatty rats remain uncertain.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…Spontaneously Diabetic Torii Lepr fa (SDT fatty) rats were established by transferring the fa allele of the Zucker fatty rat into the genome of the nonobese SDT rat. The SDT fatty rat shows hyperphagia, obesity, hyperglycaemia, and dyslipidaemia, so it can be considered a new model for obese type 2 diabetes . However, the details of the haemodynamics in SDT fatty rats remain uncertain.…”
Section: Introductionsupporting
confidence: 84%
“…Therefore, in nonclinical studies, it is very important to evaluate the efficacy of drugs in a PAD model based on metabolic syndrome animals. Masuyama et al reported that SDT fatty rats develop obesity, hyperglycaemia, and dyslipidaemia at a young age due to the transfer of the fa allele from the Zucker fatty rat to the genome of the nonobese SDT rat . In this study, we found that hindlimb blood flow was significantly lower and the plasma NOx level was significantly higher in the SDT fatty rats compared with the SD rats.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Circadian rhythms are known to be affected by food-taking behavior [ 26 , 27 ]. As our previous studies have revealed that SDT fatty rats show hyperphagia [ 28 , 29 ], this feature may underlie the deficits of circadian rhythm in the SDT fatty rats. Although there is no data on the food intake pattern of SDT fatty rats, the relatively higher SLA during the light phase may reflect the food-taking behavior.…”
Section: Discussionmentioning
confidence: 92%